Journey to the Volcano Palace - Abbott, Tony.; Merrell, David J.; Jessell, Tim (New York : Scholastic, 1999)
Eric and his friends attempt to recover a magic jewel which was stolen from Princess Keeah by Lord Sparr.
"A Little Apple paperback."
3.0
3-6
Keywords: Magic -- Fiction; Precious stones -- Fiction; Fantasy; Magic -- Fiction; Precious stones -- Fiction; Fantasy fiction